Effectiveness of Phosphodiesterase Type 5 Inhibitors for Erectile Dysfunction After Radical Prostatectomy: A Systematic Review - Maulfi Natsir (Indonesian Health Journal, 2026)
Erectile dysfunction (ED) is one of the most frequent complications following radical prostatectomy, with substantial implications for quality of life, psychological well-being, and interpersonal relationships. The pathophysiology involves a combination of cavernous nerve injury, vascular insufficiency, and structural alterations such as corporal fibrosis. Phosphodiesterase type 5 inhibitors (PDE5i) are recommended as first-line therapy; however, their effectiveness in post-prostatectomy ED remains variable and influenced by multiple clinical factors. The objective to systematically evaluate the effectiveness of PDE5 inhibitors in improving erectile function in patients with ED following radical prostatectomy. This systematic review was conducted in accordance with PRISMA guidelines. Literature searches were performed in PubMed, Scopus, and Google Scholar for studies published between 2017 and 2025. Randomized controlled trials and observational studies evaluating PDE5 inhibitors (sildenafil, tadalafil, vardenafil) in post-prostatectomy ED were included. Primary outcomes were erectile function scores (International Index of Erectile Function/IIEF) and recovery rates. The results twenty studies met inclusion criteria. PDE5 inhibitors demonstrated consistent improvement in erectile function scores across most studies (1–3). However, treatment outcomes varied significantly depending on nerve-sparing status, baseline erectile function, patient comorbidities, and timing of therapy initiation (4–7). Early initiation as part of penile rehabilitation showed potential benefits in preserving erectile function, although findings were not uniform (6,8). PDE5 inhibitors are effective in improving erectile function after radical prostatectomy, but their effectiveness is influenced by multiple interacting factors. A personalized and multimodal treatment approach is essential to optimize outcomes